2017
DOI: 10.1016/j.ajog.2017.05.054
|View full text |Cite
|
Sign up to set email alerts
|

Variations in resting energy expenditure: impact on gestational weight gain

Abstract: Background There are significant variations in gestational weight gain with many women gaining in excess of Institute of Medicine guidelines. Unfortunately, efforts to improve appropriate gestational weight gain have had only limited success. To date, interventions have focused primarily on decreasing energy intake and/or increasing physical activity. Maternal resting energy expenditure, which comprises ~60% of total energy expenditure compared with the ~20% that comes from physical activity, may be an importa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
35
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(40 citation statements)
references
References 30 publications
2
35
2
Order By: Relevance
“…The smaller increase in the current study could be explained by the shorter evaluation period. Unlike other studies that found a moderate negative correlation between REE in the 3rd trimester and total GWG [11], we only found a positive correlation between early changes in REE and GWG in the latter half of the study. Our lack of a positive association across the entire study period may be due to the small sample size or large variations in REE at each study visit.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…The smaller increase in the current study could be explained by the shorter evaluation period. Unlike other studies that found a moderate negative correlation between REE in the 3rd trimester and total GWG [11], we only found a positive correlation between early changes in REE and GWG in the latter half of the study. Our lack of a positive association across the entire study period may be due to the small sample size or large variations in REE at each study visit.…”
Section: Discussioncontrasting
confidence: 99%
“…In our study, there was an overall increase in REE throughout the study of 11.5%. This is similar to other studies that have assessed REE that found increases ranging from 13% to 35% [8,11,[15][16][17]. The large range in changes in REE throughout pregnancy is reflective of the population being studied, the body weight status prior to the study, and the duration of data collection (e.g., preconception to postpartum).…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Specific conditions expected to influence EE have been studied such as sepsis [4][5][6], burns [4,7], trauma [4,8], cerebrovascular accidents [4,9], pregnancy [10], body temperature [4], administration of sedatives [11], and therapeutic hypothermia [4,12]. An increased EE has been reported in patients with sepsis, trauma, burns, fever, and pregnancy.…”
Section: Introductionmentioning
confidence: 99%